Sequence order and date of establishment of sunflower and cassava in intercropping systems. - Dalbem, Márcio Luiz Miranda; Silva, Paulo Regis Ferreira da (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of evaluating the effect of date of establishment of sunflower and cassava in intercropping systems on yield and on use efficiency of land (UET), this work was conducted in the state of Rio Grande do Sul, Brazil. Treatments were composed by sunflower or cassava in sole cropping, with single or double rows, planted at August, 28th or at September, 29th, and sunflower and cassava intercropped in double rows, simultaneously at August, 28, with cassava planted at August, 29th, and sunflower at September, 29th, or with sunflower planted at August, 28th, and cassava at September, 29th. Root yield of cassava and achene yield of sunflower grown in intercropped systems were statisticaly similar to those obtained in sole cropping. There was no effect of relative date of establishment of sunflower and cassava in intercropping systems on yield and on UET. Results showed higher UET in intercropping systems than in sole cropping